2016
DOI: 10.1055/s-0042-114781
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic Acid Decreases Gentamicin-Resistance in Vancomycin-Resistant Enterococci

Abstract: The resistance of commensal bacteria against first and second line antibiotics has reached an alarming level in many parts of the world and endangers the effective treatment of infectious diseases. Particularly vancomycin-resistant represents an increasing clinical problem in the treatment of infectious diseases and hinders adequate antibiotic stewardship. In consideration of the lack of novel antibiotic compounds, the development of resistance-modifying agents, however, can mitigate the spread of bacterial dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
(39 reference statements)
0
11
0
2
Order By: Relevance
“…Piperine isolated from black pepper was shown to enhance antimicrobial activity of mupirocin against S. aureus strains including MASA through the inhibition of efflux of ethidium bromide (Mirza et al, 2011). In addition, Schmidt et al (2016) revealed therapeutic potential of glycyrrhizic acid in coapplication with gentamicin for defined local bacterial infections caused by vancomycin-resistant Enterococcus strains, indicating that glycyrrhizic acid improve the antimicrobial activity of gentamicin to antibiotic-resistant bacteria ( Table 1).…”
Section: Inhibition Activity Of Monomer Of Tcm Herbs On Antibiotic-rementioning
confidence: 99%
“…Piperine isolated from black pepper was shown to enhance antimicrobial activity of mupirocin against S. aureus strains including MASA through the inhibition of efflux of ethidium bromide (Mirza et al, 2011). In addition, Schmidt et al (2016) revealed therapeutic potential of glycyrrhizic acid in coapplication with gentamicin for defined local bacterial infections caused by vancomycin-resistant Enterococcus strains, indicating that glycyrrhizic acid improve the antimicrobial activity of gentamicin to antibiotic-resistant bacteria ( Table 1).…”
Section: Inhibition Activity Of Monomer Of Tcm Herbs On Antibiotic-rementioning
confidence: 99%
“…Multi-drug therapy is less vulnerable to adaptive resistance due to biological systems being less able to compensate effects from two or more substances or from one substance that acts on multiple targets simultaneously [33]. A shift in the way chemotherapy has been approached in the last few years indicates that multidrug therapies are going to replace mono-substance therapies in the near future as the standing paradigm [34].…”
Section: Resultsmentioning
confidence: 99%
“…Much of researches in antibacterial effect have found that licorice can exert antibacterial effects by inhibiting pathogenic bacteria and reducing the bacterial gene expression. For instance, 2.4 mM glycyrrhizin decreased the minimum inhibitory concentration (MIC) of gentamicin from >8 mg/L to ≤0.125 mg/L (Schmidt et al, 2016). Long investigated the antibacterial effect of glycyrrhizin on methicillin-resistant Staphylococcus aureus (MRSA) in a mouse model of skin infection.…”
Section: Antibacterial and Antifungal Effectsmentioning
confidence: 99%